2002
DOI: 10.1136/vr.151.11.324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tissue reactions in the skin and body wall of koi (Cyprinus carplo) to five suture materials

Abstract: Five different suture materials (silk, monofilament nylon, polyglyconate, polyglactin 910, and chromic gut) were placed in the skin and body wall of 10 Doitsu (scaleless) koi (Cyprinus carpio). After seven days the sutures were retrieved from five of the fish in 5 mm and 6 mm punch biopsies, and after 14 days they were retrieved in the same way from the other five. The tissue reactions were evaluated by gross visual inspection and by histological examination. The total inflammatory reaction was graded on a sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 17 publications
6
46
0
2
Order By: Relevance
“…This suggested that the effects of surgically implanted transmitters on growth of bighead carp had almost disappeared 28 days after surgery. Monofilament suture may reduce wicking of bacteria into the peritoneal cavity and elicit a lesser foreign body response (Hurty et al 2002), thus minimizing inflammation in the body wall and enabling sutures to remain intact longer (Deters et al 2010). In the current study, all incisions were healed 56 days after surgery, but the sutures were partially retained in incisions, causing additional incision infection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the effects of surgically implanted transmitters on growth of bighead carp had almost disappeared 28 days after surgery. Monofilament suture may reduce wicking of bacteria into the peritoneal cavity and elicit a lesser foreign body response (Hurty et al 2002), thus minimizing inflammation in the body wall and enabling sutures to remain intact longer (Deters et al 2010). In the current study, all incisions were healed 56 days after surgery, but the sutures were partially retained in incisions, causing additional incision infection.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues were routinely processed, embedded in paraffin, sectioned at 5 microns, stained with hematoxylin and eosin (HE), and examined by light microscopy. Lesions were scored by a single pathologist according to the scale outlined in Hurty et al (2002). In brief, lesions were scored from 0 (no remarkable microscopic abnormalities) to 5 (severe lesions) for each lesion type.…”
Section: Methodsmentioning
confidence: 99%
“…The most common suture material currently used for surgeries involving fish is synthetic monofilament (Wagner and Cooke 2005), which has been shown to minimize tissue inflammation compared to other suture types in several fish species. These suture comparison studies have included rainbow trout Oncorhynchus mykiss (range of 394-618 mm and 700-2,980 g, Kaseloo et al 1992; mean 306 mm and 338 g, , tilapia Oreochromis aureus (range of 574-1,033 g, Thoreau and Baras 1997), Chinook salmon (range of 95-121 mm, Deters et al 2010) and koi Cyprinus carpio (average 94 g, Hurty et al 2002).…”
Section: Suture Materialsmentioning
confidence: 99%